THE STUDY OF THE CASE : THE MASTER PLAN OF URBAN TRANSPORT FOR THE AREA OF METROPOLITAN LIMA - CALLAO IN THE REPUBLIC OF PERU - Mamani Mocedo, Néstor Adolfo (2008)
The metropolitan area of Lima - Callao is located in the center of Peru, facing the Pacific Ocean. Lima is the capital and serves as political and administrative centre of the country. The Callao is the main seaport of Perú and one of the most important of South America. Both, the city of Lima and Callao are autonomous and, according to the Law have the same powers. Consequently, any solution to the problem of transportation of Lima is necessarily linked to a solution of the transportation of Callao. Indeed, from a social, economic and cultural perspective the two cities are an unit. Therefore, it is very important to develop a Transport Master Plan in the metropolitan area of Lima - Callao. The Master Plan developed by Yachiyo Engineering Co. Ltd. define specific plans for: Roads, Raíl, Trunk Bus, and Traffic Management, identifying for each relevant projets of transportation for 2025 and 2010.